The bHLH Domain of Mist1 is Sufficient to Activate Gene Transcription - Tran, Thai (Gene Expr, 2018)
Mist1 is a tissue-specific basic helix–loop–helix (bHLH) transcription factor that plays an essential role in maintaining and organizing the exocrine pancreas. Consequently, mice lacking Mist1 exhibit disrupted acinar cellular polarity and defective zymogen granule trafficking. Despite extensive studies demonstrating a requirement for Mist1 in exocrine pancreas development and function, little is known about the molecular targets for Mist1 interaction and the mechanism(s) of how Mist1 regulates gene transcription. To address these deficiencies, a series of molecular studies was performed to identify the preferred Mist1 dimer complex and to establish the preferred DNA binding site for this bHLH factor. In vivo coimmunoprecipitation assays confirmed that the functional Mist1 complex in pancreatic acinar cells was a Mist1 homodimer that bound to a unique DNA target site known as the TA-E-box. Binding of Mist1 to a TA-E-box-regulated promoter led to transcriptional activation of the target gene. Surprisingly, Mist1 truncations containing only the central bHLH domain retained approximately 80% of transcriptional activity. Coimmunoprecipitation studies demonstrated that the bHLH domain interacted with coactivators belonging to the p300/CBP family, suggesting that Mist1 activates exocrine-specific gene transcription through an acetylation mechanism.